Johannine Christology - Porter, Stanley E.; Pitts, Andrew W. (Johannine Studies, 2020)
Johannine Christology provides a snapshot of the foremost investigations of this important topic by a selection of scholars representing a range of expertise in this field. The volume is organized into four major parts, which are concerned with the formation of Johannine Christology, Johannine Christology in Hellenistic and Jewish contexts, Christology and the literary character of the Johannine writings, and the application of Christology for the Johannine audience and beyond. The fifteen contributors to this volume comprise an international set of Johannine scholars who explore various ways of both describing and then pursuing the implications of Johannine Christology. Their contributions focus primarily upon the Gospel, but involve other key texts as well.